Relationship Between Akkermansia muciniphila Abundance and Exercise-Induced Fat Mass Reduction - Chmurska, Agnieszka; Majchrzyk, Aleksandra; Strzępek, Aleksandra; Smerdzyński, Mateusz; Janaszek, Agnieszka; Kałuża, Kinga; Frączek, Karolina; Łyżwa, Julia; Pater , Michał; Kałwa, Natalia (Quality in Sport, 2026)
Background: Obesity is a major health concern linked to type 2 diabetes, cardiovascular diseases, and NAFLD. Growing evidence highlights the role of gut microbiota dysbiosis in these disorders. Akkermansia muciniphila, a mucin-degrading bacterium, is inversely associated with adiposity, inflammation, and insulin resistance. Physical activity improves metabolic health, but variability in outcomes suggests additional modulators, including gut microbiota. Aim: This review aimed to summarize the relationship between A. muciniphila, physical exercise, and fat mass reduction, and to examine underlying physiological and microbiological mechanisms. Materials and Methods: A structured narrative review with elements of systematic analysis was conducted. Databases (including PubMed) were searched for experimental and clinical studies assessing associations between A. muciniphila and metabolic parameters, the effects of exercise on gut microbiota, and mechanisms linking microbiota changes with metabolic outcomes. Both animal and human studies were included. Results: Animal studies consistently show that aerobic and moderate exercise increase A. muciniphila abundance, enhance microbial diversity, improve glucose tolerance, and reduce fat mass. Human studies show more variable results, with modest increases in A. muciniphila and metabolic improvements, particularly in overweight or metabolically impaired individuals. Proposed mechanisms include improved gut barrier integrity, immune modulation, increased short-chain fatty acid production, AMPK activation, and microbiota–adipose tissue cross-talk. Conclusions: Physical activity modulates gut microbiota, with A. muciniphila as a potential mediator of exercise-induced fat loss and metabolic improvement. Although human evidence is heterogeneous, targeting this bacterium through exercise and lifestyle interventions may support obesity prevention and metabolic health.